The Role of Ontology in Developing Language Skills - Nur Nilam Sari; Dewi Permata Sari; Taufiqurrahman Taufiqurrahman; Bahri Arifin (Yayasan Pendidikan Bima Berilmu, 2025)
Language learning transcends mere vocabulary acquisition and grammatical understanding, encompassing the intricate interplay between language, thought, and existence. This research investigates how ontological perspectives-realism, idealism, and constructivism-shape language education practices and influence learners' cognitive and linguistic development. Employing a literature review methodology, the study synthesizes contemporary research to elucidate the relationship between ontological beliefs and effective language skill development. Realism, with its emphasis on objective knowledge and standardized assessment, promotes structured language instruction but may stifle creativity and contextual relevance. In contrast, idealism encourages learners to engage with language as a vehicle for expressing personal and cultural identities, fostering critical thinking and collaborative learning. Constructivism emphasizes active engagement and social interaction, positioning language acquisition as a dynamic process rooted in real-world contexts. The findings underscore the need for educators to reflect on their ontological assumptions, balancing structured approaches with those that prioritize meaning and interaction. By integrating diverse ontological perspectives, language education can cultivate proficiency and facilitate meaningful communication, preparing learners for real-world linguistic challenges. This research offers valuable insights for educators, informing curriculum design and teaching strategies to enhance language learning experiences.